A System's View of E‐Learning Success Model. (26th January 2018) - Eom, Sean B.; Ashill, Nicholas J.
ABSTRACT: The past several decades of e‐learning empirical research have advanced our understanding of the effective management of critical success factors (CSFs) of e‐learning. Meanwhile, the proliferation of measures of dependent and independent variables has been overelaborated. We argue that a significant reduction in dependent and independent variables and their measures is necessary for building an e‐learning success model, and such a model should incorporate the interdependent (not independent) process nature of e‐learning success. We applied structural equation modeling to empirically validate a comprehensive model of e‐learning success at the university level. Our research advances existing literature on CSFs of e‐learning and provides a basis for comparing existing research results as well as guiding future empirical research to build robust e‐learning theories. A total of 372 valid unduplicated responses from students who have completed at least one online course at a university in the Midwestern United States were used to examine the structural model. Findings indicated that the e‐learning success model satisfactorily explains and predicts the interdependency of six CSFs of e‐learning systems (course design quality, instructor, motivation, student‐student dialog, student‐instructor dialog, and self‐regulated learning) and perceived learning outcomes.